A decomposition methodology for dynamic modeling of cold box in offshore natural gas liquefaction process. (4th January 2016) - Lee, Chul-Jin; Song, Kiwook; Lee, Yongseok; Han, Chonghun
Highlights: We present a novel methodology for dynamic modeling of cold box. A decomposition algorithm for adjusting k and UA value is suggested. The methodology is validated with the offshore natural gas liquefaction process. It can be applied to other process designs requiring dynamic modeling of cold box. Abstract: Natural gas liquefaction process using mixed and/or cascade refrigerant is popular in onshore LNG (liquefied natural gas) plant. Similar attempt has been adopted for FLNG (floating LNG) but still needed for the improvement of the process to enhance its efficiency as well as reliability. The dynamic modeling of cold box which is a core equipment in LNG/FLNG plant enabling to liquefy natural gas is crucial in order to develop or improve a liquefaction process concerning operability and controllability. A decomposition methodology for dynamic modeling of cold box in the case of lack of internal design data at early design stage is presented. The proposed methodology is validated through the industrial application of offshore natural gas liquefaction process and expected to be extensively applied to the various process designs which require dynamic simulation of cold box unit.